2008
DOI: 10.1007/s00429-008-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of local GABAergic influences on the HPA axis

Abstract: Neuronatomical and pharmacological studies have established GABA-mediated inhibition of the HPA axis at the level of the PVN. The origin of this innervation is a series of local hypothalamic and adjacent forebrain regions that project to stress-integrative hypophysiotropic CRH neurons. While a role in tonic inhibition of the stress axis is likely, this system of inhibitory loci is also capable of producing a dynamic braking capacity in the context of the neuroendocrine stress response. The latter function is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
207
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(220 citation statements)
references
References 54 publications
6
207
0
7
Order By: Relevance
“…Our findings of a higher HPA-system sensitivity in more anxious individuals after HF-rTMS applied over the right DLPFC might be especially germane in light of the therapeutic applications of rTMS as a treatment for anxiety disorders and/or posttraumatic stress disorder (PTSD) (Cohen et al, 2004;Pallanti and Bernardi, 2009;Zwanzger et al, 2009;Handwerger, 2009;Yue et al, in press). Because of the overwhelming evidence that GABAergic mechanisms regulate neuroendocrine stress responses (Herman et al, 2002;Herman et al, 2004;Kovács et al, 2004;Cullinan et al 2008;Radley et al, 2009) and the importance of GABA receptor involvement in the pathophysiology and treatment of anxiety disorders (Lydiard, 2003;Nemeroff, 2003;Kalueff and Nutt., 2007), it is tempting to assume that in our study the observed HPA-axis sensitivity to one HF-rTMS session in more anxious females was mediated by the GABA system.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of a higher HPA-system sensitivity in more anxious individuals after HF-rTMS applied over the right DLPFC might be especially germane in light of the therapeutic applications of rTMS as a treatment for anxiety disorders and/or posttraumatic stress disorder (PTSD) (Cohen et al, 2004;Pallanti and Bernardi, 2009;Zwanzger et al, 2009;Handwerger, 2009;Yue et al, in press). Because of the overwhelming evidence that GABAergic mechanisms regulate neuroendocrine stress responses (Herman et al, 2002;Herman et al, 2004;Kovács et al, 2004;Cullinan et al 2008;Radley et al, 2009) and the importance of GABA receptor involvement in the pathophysiology and treatment of anxiety disorders (Lydiard, 2003;Nemeroff, 2003;Kalueff and Nutt., 2007), it is tempting to assume that in our study the observed HPA-axis sensitivity to one HF-rTMS session in more anxious females was mediated by the GABA system.…”
Section: Discussionmentioning
confidence: 99%
“…However, GABA and myo-Ins concentrations were also lower relative to the rat hippocampus, whereas these metabolites had significantly higher levels in the mouse hypothalamus relative to the hippocampus (Lei et al, 2010). g-Aminobutyric acid is known to have an important inhibitory role in the regulation of the hypothalamic-pituitary-adrenocortical axis (Cullinan et al, 2008) and especially at the level of the paraventricular nucleus (Cullinan et al, 2008). No GABAergic neurons are located within the PVN itself (Cullinan et al, 2008), which may explain the lower GABA levels measured compared with the hippocampus in healthy rats.…”
Section: Comparison Of the Neurochemical Profiles Of The Hypothalamusmentioning
confidence: 99%
“…g-Aminobutyric acid is known to have an important inhibitory role in the regulation of the hypothalamic-pituitary-adrenocortical axis (Cullinan et al, 2008) and especially at the level of the paraventricular nucleus (Cullinan et al, 2008). No GABAergic neurons are located within the PVN itself (Cullinan et al, 2008), which may explain the lower GABA levels measured compared with the hippocampus in healthy rats. In response to changes in brain homeostasis, metabolite concentrations in the hippocampus and the hypothalamus increased.…”
Section: Comparison Of the Neurochemical Profiles Of The Hypothalamusmentioning
confidence: 99%
“…Furthermore One other important aspect of the negative feedback on HPA axis is the effect of glucocorticoids on limbic areas, which is mediated by local GABAergic inputs to the CRH neurons (Bali & Kovacs 2003, Cole & Sawchenko 2002, Cullinan et al 2008, Miklos & Kovacs 2002). …”
Section: Glucocorticoid Negative Feedback On Crh In the Pvhmentioning
confidence: 99%